Parallelism of the Occlusal Plane with the Ala-tragus Line in Various Posterior References in Dentate Patients - Negareh Salehabadi; Navid Pournasiri; Tahmineh Bamdadian; Kosar Dadgar; Hadi Mokhtarpour; Alireza Khalilian; Mohammad Ebrahimi Saravi (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Occlusal plane in edentulous patients is lost and needs to be reconstructed. The most common method for reconstructing occlusal plane is to make it parallel to the ala-tragus line. There are disagreements about the posterior reference of ala-tragus line. The aim of this study was to determine the best posterior reference of ala-tragus line (superior, middle and anterior references) for reconstructing occlusal plane. Materials and methods: In this descriptive-analytical study, 150 dentate patients with class I relationship enrolled. Patients were placed 1.5 meters from the camera and their head was in NHP mode and symmetrical to the line perpendicular to the horizon. Fox-plane was placed in contact with central incisors and first molars of maxilla and imaging was performed from the right side of the face. The angles required were then measured using AutoCAD 2020. Results: There were 75 male and 75 female patients (mean age= 23.05±1.69 years) and the mean OT1-OP angle was 8.75, which was the closest to the mean OT1-AT3 angle (8.85). This finding also was repeated in both men and women. Among all patients, OT1-AT3 angle was found to have the highest proximity to the occlusal plane (61. 33%), 53.34% in men and 69.33% in women. Conclusion: Inferior point on the tragus of the ear in ala-tragus is the best reference for reconstructing the occlusal plane during construction of a removable denture for male and female edentulous patients.